Morphology of the head-associated exocrine glands in Cornitermes cumulans with the description of a novel gland for the worker caste - Costa-Leonardo, Ana Maria [UNESP]; Janei, Vanelize [UNESP]; Bacci, Lorena Maria Gardesani [UNESP]; Silva, Iago Bueno da (Elsevier, 2025)
Exocrine glands are important mediators of communication in eusocial insects and the description of novel glands reflects the complex context in which these animals live. Here we revisit the head-associated glands in workers of the Neotropical termite Cornitermes cumulans through histological analysis and describe a novel gland for this caste, the intramandibular glands. This structure is located underneath the cuticle of the dorsodistal part of each mandible. The glands showed an epithelial arrangement, but the cytological morphology is complex, comprising classes I and III of secretory cells. The present data highlight the importance of the intramandibular glands in the worker caste and demonstrate different morphology of these glands in Isoptera, probably related to the specialized function of the castes. Features of active glandular activity were also observed in the mandibular, labral, and salivary glands of these workers. Despite the intramandibular glands being also found in workers of other social insects, their occurrence in termites was restricted to the soldier caste of Machadotermes. Even so, their cytological structure differs from those of C. cumulans workers. The likely function of the worker intramandibular glands is discussed considering the separate-nest life type present by C. cumulans and tasks performed by workers. The chemical nature of the secretion and the occurrence of the glands in other termite taxa still require further investigation.
Keywords: Histology; Intramandibular glands; Isoptera; Termitidae